The Religious Reform movement in Europe and its most famous pioneers - خزامة, عاطف; أيمن صلاط (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
The reformation movement in Europe did not occur suddrenly, Rather the catholic church was subjected to several reform movementes over the previous centuries, but it was going through them peacefully until the sixtieenth century AD came when the papacy lost its prestige, the popes became agroup that owned and collected money and cared about it more than they cared about the affaires of the church, as it became their own interests, and the interests of their relatives and those in whom they seek refuge have also become their concerns to a greater extent than matters of doctrine and the catholic church, which prompted thinkers and reformers to research the conditions of the catholic church and the necessity of reforming itself on its own from the inside, and in the event that it is unable toreform internally, reform is imposed on it from the outside, and it must accept that, despite what is imposed, one of the means of reform since it was not able to do so on its own. The religious revolution began in Germany because the philosophy of theology and religious beliefs were more firmly established there than in Italy, where the headquarters of the papacy was.